A Morphological Analysis of Derivational Suffix in the Short Story “How to Become a Writer” by Lorrie Moore - Hutasoit, Mikhael Parlindungan (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2025)
The limited understanding of English word formation processes among language learners constitutes a persistent impediment to vocabulary acquisition and textual comprehension. This study examines the deployment of derivational suffixes in Lorrie Moore's short story "How to Become a Writer." As a fundamental component of English morphological processes, derivational suffixes generate novel lexical items while simultaneously effectuating transformations in the grammatical categorization and semantic properties of base forms, thereby augmenting learners' lexical repertoire and interpretive proficiency. Employing a descriptive qualitative paradigm, the corpus was systematically extracted from the aforementioned literary work and subsequently categorized according to their morphosyntactic transitions, encompassing verbal to nominal, adjectival to nominal, nominal to verbal, nominal to adjectival, verbal to adjectival, and adjectival to adverbial conversions. The analysis endeavors to elucidate how derivational suffixes instigate modifications in both the morphological configuration and semantic orientation of words within the textual context. The results show that derivational suffixes are frequently used in the short story and play an important role in forming new words that support the meaning of the narrative. The use of derivational suffixes helps express actions, qualities, and situations more clearly in the story. This study also shows that literary texts can be useful sources for learning morphology because they provide real examples of word formation in context. It is expected that this research can help students better understand derivational suffixes and improve their English vocabulary learning.